1997
DOI: 10.1095/biolreprod56.2.549
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor α Gene Expression in the Rat Testis: Potential Role during the Prophase of Meiosis and in the Transition from Round to Elongating Spermatids

Abstract: Mutational studies have identified retinoic acid receptor alpha (RAR alpha) as having an essential role in spermatogenesis. The objective of this study was to determine which cells express RAR alpha within the normal rat testis by conducting in situ analyses for mRNA and protein. Characterization of RAR alpha expression revealed the time and location of the vitamin A requirement during spermatogenesis. In situ hybridization analysis of testis from adult rats showed the highest level of transcripts occurring in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
62
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 40 publications
6
62
0
Order By: Relevance
“…First, the expression patterns of retinoic acid receptors, retinoic acid synthesizing enzymes, and other retinoid binding proteins in the testis differ between the rat (Akmal et al, 1997;Zhai et al, 2001;Rajan et al, 1990) and the mouse (Vernet et al, 2006). Second, the outcome of VAD in the seminiferous epithelium differs between these species: in VAD rats, spermatogenesis is arrested at the preleptotene spermatocyte stage (Huang and Humbree, 1979;Huang et al, 1990;Ismail et al, 1990), whereas in VAD mice, it is arrested at the spermatogonia stage (Huang and Hembree, 1979;Gaemers et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the expression patterns of retinoic acid receptors, retinoic acid synthesizing enzymes, and other retinoid binding proteins in the testis differ between the rat (Akmal et al, 1997;Zhai et al, 2001;Rajan et al, 1990) and the mouse (Vernet et al, 2006). Second, the outcome of VAD in the seminiferous epithelium differs between these species: in VAD rats, spermatogenesis is arrested at the preleptotene spermatocyte stage (Huang and Humbree, 1979;Huang et al, 1990;Ismail et al, 1990), whereas in VAD mice, it is arrested at the spermatogonia stage (Huang and Hembree, 1979;Gaemers et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The different fates of preleptotene spermatocytes in mouse and rat under VAD conditions may be related to differences in expression of RAR and, thus, in RA responsiveness. In fact, rat spermatocytes express Rara (Akmal et al, 1997), whereas no Rar (a, b, and g) is detected in their mouse counterparts (de Rooij et al, 1994;Vernet et al, 2006).…”
Section: Vitamin a Does Not Exert Major Functions In Mouse Spermatocymentioning
confidence: 94%
“…Thus, it is likely that these factors also play a role in the lack of synchronization of gonocyte progression to spermatogonia, within the few days encompassing this process. It is not known whether, in vivo, RA induces differentiation by acting directly on the germ cells or if it is an indirect process involving Sertoli cells, as both cell types express RA receptors (RARs) and retinoid X receptors (RXRs) at varying levels (Akmal et al 1997, de Rooij & Russell 2000. It has been shown that at PND3, gonocytes express all isoforms of RARs and RXRs, mainly high levels of RARA and RXRA, whereas Sertoli cells express mainly RXRG (Boulogne et al 1999).…”
Section: Transitional Gonocyte Differentiation In Rodentsmentioning
confidence: 99%
“…In the female fetus, it has been considered that a significant number of germ cells enter meiotic prophase to characterize the transition of oogonia into oocytes under the increasing secretion of folliclestimulating hormone (FSH) and luteinizing hormone. Since the peak level of gonadotropin secretion correlates with the peak level of oogonial multiplication in the fetus (4,(12)(13)(14)(15) and FSH levels are much lower in the male fetus than in the female, it has been considered that the initiation of meiosis in the fetal ovary is dependent on FSH (11).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it appears most likely that a meiosis-preventing substance(s) is present in fetal and infantile seminiferous tubules. On the other hand, c-mos proto oncogene, maturationpromoting factor and mitogen-activated protein kinase have been recently reported as possible localized factors for the initiation and progression of meiosis, because they are expressed during the meiosis of germ cells (12)(13)(14). …”
Section: European Journal Of Endocrinology (1999) 140mentioning
confidence: 99%